SAT0042 Evidence of netosis in circulating neutrophils and skin lesions with vasculitis and panniculitis in behÇet's disease. (12th June 2018) - Kallas, R.; Safi, R.; Hamam, R.; Uthman, I.; Nassar, D.
Abstract : Background: Behcet's disease (BD) pathophysiology is poorly understood. It is characterised by recurrent episodes of acute inflammation consisting of neutrophil infiltration in affected organs and around blood vessels. Recently, NETosis, traping and killing pathogens by activated neutrophils, has been described. These Neutrophil Extracellular Traps (NETs) were shown to promote inflammation in a number of autoimmune diseases such a Systemic Lupus Erythematosus), ANCA-Associated Vasculitis and Rheumatoid Arthritis. We hypothesise that in BD, neutrophils trigger inflammation and vasculitis via NETosis. Objectives: The aim of this study is to demonstrate the implication of NETosis in the pathophysiology of this disease. Methods: Blood specimens from BD patients and matched healthy volunteers were collected at the American University of Beirut Medical Centre. Circulating neutrophils were isolated and cultured in Roswell Park Memorial Institute (RPMI) 1640 medium. Cultured cells were treated with colchicine, dexamethasone or corresponding vehicle, and stimulated with serum from BD patients, controls or left unstimulated. The kinetic and amount of NET formation was assessed by cell counting using Hoechst 33 342 and Sytox green staining and fluorescent microscopy. Moreover, previously described NET-bound proteins (elastase, myeloperoxidase, citrullinated histone-3 and PR-3) were identified by immunolabeling and mRNA expression levels of PAD4, a key enzyme that promotes citrullination of arginine residues on chromatin, was evaluated in neutrophils from BD compared to controls. Finally, evidence of NETosis in vivo was assessed on paraffin embedded specimens from damaged organs of BD patients using immunolabeling and confocal microscopy. Results: The percentage of unstimulated neutrophils undergoing NETosis in vitro was significantly higher in BD patients compared to controls. Treatment of unstimulated BD neutrophils with colchicine and dexamethasone resulted in significant decrease in NETs formation compared to controls. Interestingly, the percentage of NETs increased upon exposure of neutrophils to serum from BD patients. Moreover, PAD4 mRNA expression was 3 times higher in BD patients compared to controls. Immunolabeling assay demonstrated that NET-bound proteins were present in NETs scaffold of unstimulated neutrophils from BD patients in vitro . Additionally, NETs were detected in skin tissues of BD patients focally distributed in proximity to small vessels in vasculitis patients and to inflamed adipose tissue in panniculitis patients. These were associated with elastase and citrullinated histone-3 proteins. Conclusions: We show here for the first time that circulating neutrophils from BD patients are prone to NETosis in vitro . NET formation was inhibited by the addition of colchicine and dexamethasone reflecting their therapeutic benefits in BD. The increase of NETosis upon serum stimulation suggests the presence of soluble factors and cytokines triggering NETs in BD. Combined, these results suggest a major role of NETs in the pathophysiology of BD. Reference: [1] Kessenbrock K, et al. Netting neutrophils in autoimmune small-vessel vasculitis. Nature Medicine2009;15:623–625. Disclosure of Interest: None declared